(untitled) - Venneri, Alexi (Hoboken, N.J., 2005)
America's small and midsized businesses face unique challenges as they struggle to reach the kind of long-term business goals achieved by larger companies. Balls! shows that successful firms follow certain rules and display six essential traits-they are brave, authentic, loud, lovable, and spunky. Add an exclamation mark for "Do It Right Now Before Someone Else Does!" and that spells Balls!-something all growing businesses need in order to truly succeed. Written by a young executive at one of America's fastest growing small businesses, Balls! looks at business success from a decidedly exuberant and creative perspective, bringing fresh ideas and tactics that any business leader, in any industry, will find immediately useful.
Keywords: Success in business,Thành công trong kinh doanh